Effects of repetitive imagination of alcohol consumption on craving in alcohol-dependent patients: A pilot study. (December 2016) - Geisel, Olga; Behnke, Julia; Schneider, Michael; Wernecke, Klaus-Dieter; Müller, Christian A.
Abstract: Background: In the majority of patients with alcohol use disorder (AUD), the clinical course is characterized by multiple relapses to drinking, frequently preceded by intense craving for alcohol. The present pilot study aimed to assess the effects of a repetitive imaginary cue-exposure protocol in reducing craving in recently abstinent alcohol-dependent patients. Methods: Sixty-four patients were randomly assigned to six intervention groups and were instructed to repetitively imagine: i) drinking a glass of their preferred alcoholic drink (low vs. high number of repetitions); or ii) drinking a glass of water (low vs. high number of repetitions); or iii) performing an analogous movement or performed no imagination. Additionally, 10 healthy controls were instructed to repetitively imagine drinking a glass of their preferred alcoholic drink (high number of repetitions). The levels of craving before and after intervention were measured using the Alcohol Urge Questionnaire (AUQ) and the Visual Analogue Scale for Craving (VASC). Results: Repetitive imagination of alcohol consumption did not lead to a significant decrease in craving in alcohol-dependent patients as measured by the AUQ and VASC. In contrast, healthy controls showed a nearly significant decrease of the urge to drink alcohol after applying the protocol with a high number of repetitions. Conclusions: The findings of this pilot study might indicate an aberrant ability to habituate to alcohol-related stimuli in patients with AUD compared to healthy subjects. Future studies in larger samples are needed to further explore the effectiveness of imaginary cue-exposure interventions in alcohol dependence.